1990
DOI: 10.1002/chir.530020102
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of halazepam by rat liver microsomes: Stereoselective formation and n‐dealkylation of 3‐hydroxyhalazepam

Abstract: Metabolism of halazepam [7-chloro-1,3-dihydro-5-phenyl-1-(2,2,2-trifluoroethyl)-2H-1,4-benzod iazepin- 2-one, HZ] was studied by incubation with liver microsomes prepared from untreated, phenobarbital (PB)-treated, and 3-methylcholanthrene (3MC)-treated male Sprague-Dawley rats. Metabolites of HZ were separated by normal-phase HPLC. Relative rates of HZ metabolism by liver microsomes prepared from untreated and treated rats were PB-treated much greater than untreated greater than 3MC-treated at low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…However, not even this procedure enabled us to solubilize pinazepam, prazepam or balazepam in incubation media at concentrations bigh enough for enzyme kinetic studies. Recent reports with both prazepam (5) and halazepam (6) involved the use of methanolic solutions of substrates, which our results do not support for kinetic studies, though this may not have compromised the investigation of stereochemical factors for wbicb the cited studies were designed. The present method differed from that of Inaba et al (11) only in respect of the technique used for introduction of substrate, and in our use of an HPLC method for benzodiazepine analysis, as opposed to their GC method.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…However, not even this procedure enabled us to solubilize pinazepam, prazepam or balazepam in incubation media at concentrations bigh enough for enzyme kinetic studies. Recent reports with both prazepam (5) and halazepam (6) involved the use of methanolic solutions of substrates, which our results do not support for kinetic studies, though this may not have compromised the investigation of stereochemical factors for wbicb the cited studies were designed. The present method differed from that of Inaba et al (11) only in respect of the technique used for introduction of substrate, and in our use of an HPLC method for benzodiazepine analysis, as opposed to their GC method.…”
Section: Resultscontrasting
confidence: 53%
“…We bave demonstrated in the studies reported bere that diazepam, pinazepam, prazepam and halazepam do not bave sufficient solubility in microsomal incubates to render useful metabolic studies practicable with presently available product detection methodologies (Table III). Some workers (4)(5)(6) have utilized quantities of organic solvents to overcome this difficulty. We have shown, bowever, that a combination of two commonly used solvents, acetone and propylene glycol, substantially inhibits metabol-ism of diazepam by both the N-demethylation and the C3-bydroxylation pathways (Table IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Following evaporation of D17P3, OX highly enriched in either (R)-or (S)-enantiomer was dissolved in either a pure solvent or a solvent mixture for the determination of racemization tlh. Racemization half-lives were determined using 23 organic solvents potentially useful in CSP-HPLC separation of OX enantiomers (Table 1).…”
Section: Stability Of Ox Enantiomers In Various Organicmentioning
confidence: 99%
“…Immediately afterward, changes of ellipticity (A@, in millidegrees) were recorded at a wavelength (255,310,320, or 330 nm) as a function of time at ambient temperature on a JASCO Model 500A spectropolarimeter uapan Scientific Co., Easton, MD). [7][8][9][10] The monitoring wavelength was chosen to avoid strong absorption by the solvent. The tlh was determined by plotting log (A@) versus time.…”
Section: Kinetics Of Racemizationmentioning
confidence: 99%